Case report: Long-term survival in synchronous double primary malignancies of lung adenocarcinomas and esophageal squamous cell carcinoma treated with definitive chemoradiotherapy and SBRT combined with anti-PD-1 - Zeng, Rui; Zhou, Xiaoyun; Ou, Kexin; Chen, Wei; Yang, Chen; Wang, Ting; Li, Yani; Zha, Yawen; Li, Minying; Zhang, Jingjing (Frontiers in Immunology, 2025)
BackgroundThe occurrence of multiple primary cancers has become common, and the treatment of such patients is very complex, so it is necessary to combine a variety of individualized treatment methods to achieve better treatment results.Case descriptionThis report describes a patient with double primary tumors of lung and esophageal cancer had more than 36 months survival with non-operation treatment. The patient diagnosed as lung adenocarcinomas (LADC) and esophageal squamous cell carcinoma (ESCC), was treated with albumin-bound paclitaxel, nedaplatin, and anti-programmed death 1 (anti-PD-1). The esophageal lesions achieved complete response (CR) after finishing two courses of induction chemotherapy combined with anti-PD-1 followed by definitive chemoradiotherapy (CRT). Radiation pneumonitis (RP) occurred one month after the completion of CRT. The pneumonia was relieved after dexamethasone and moxifloxacin treatment. Then, the lung lesion was treated with oral chemotherapy followed by stereotactic body radiation therapy (SBRT). As of July 2024, the patient has survived for more than 3 years after the above treatments, and the current efficacy evaluation is CR of esophageal lesions, PR of pulmonary lesions.ConclusionThe multi-modality approach of systemic therapy combined with localized radiotherapy is an effective treatment in the patients of the double primary malignant tumors of LADC and ESCC. The safety and toxicity of radiotherapy for the thoracic double primary tumors demonstrate acceptability.